Study Of Wheat Flour And Tubers With The Addition Of Glycerol Monostearate - Reny Dian PS; Dedin Finatsiyatull Rosida (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
Bread is a food made from wheat flour which can be used as an alternative food substitute. Wheat flour is made from wheat which is still imported. Therefore, one way to reduce the increase in import numbers is by using local food ingredients that can be used as raw materials for making white bread. Local food ingredients that can be used are cassava tubers, kimpul tubers, uwi tubers. The use of local food ingredients as ingredients for making white bread can add variety to white bread and increase the value of white bread. The purpose of this study was to determine the effect of the proportions of wheat flour and tuber flour and the addition of glycerol monostearate on the volume of white bread rising. The results of this study used a completely randomized design (CRD) with 2 factors with 3 replications. The first factor was the proportion of wheat flour and tuber flour (cassava, kimpul, cassava) (70:30) and the second factor was the addition of glycerol monostearate (2%, 4%, 6%). The results of the best treatment were white bread and uwi flour with the addition of 6% glycerol monostearate, which had a water content of 22.705%, starch content of 40.174%, and swelling volume of 83.623%.